Toll-like Receptor and Hepatitis B Virus Clearance in Chronic Infected Patients: A Long-Term Prospective Cohort Study in Taiwan - Wu, Jia-Feng; Chen, Chien-Hung; Ni, Yen-Hsuan; Lin, Ying-Ting; Chen, Huey-Ling; Hsu, Hong-Yuan; Chang, Mei-Hwei (The Journal of infectious diseases, 2012)
Background. We sought to elucidate the impacts of the Toll-like receptors (TLRs) on spontaneous hepatitis B virus (HBV) e antigen (HBeAg) and hepatitis B s antigen (HBsAg) seroconversion in chronic HBV-infected patients. Methods. Human TLR2, TLR4, TLR5y and TLR9 gene polymorphisms were assessed in 278 HBeAg-positive, chronic HBV-infected patients. Additionally, HBV core antigen (HBcAg) in vitro stimulation using peripheral blood mononuclear cells (PBMCs) from 113 patients was done to assess interferon γ (IFN-γ) production. Results. Of the study subjects, 204 (73.4%) developed spontaneous HBeAg seroconversion, 21 (7.6%) developed spontaneous HBsAg clearance, and 10 (3.6%) had spontaneous HBsAg seroconversion during the 19.1 ± 9.9 years of follow-up. The T allele at TLR5 rs5744174 (p. Phe616Leu) and the C allele at TLR9 rs5743836 promoter predicted earlier HBeAg seroconversion (hazard ratios [HRs], 2.45 and 3.65; P= .04, and .006, respectively). The TLR5 rs5744174 T allele carriers have higher PBMCs IFN-γ secretion to HBcAg stimulation (P = .0002). The G allele carriers at TLR4 rs4986790 (p. Asp299Gly) predicted spontaneous HBsAg seroclearance (HR, 18.73; P<.001) and seroconversion (HR, 43.45; P <.001). Conclusions. Toll-like receptor 5 rs5744174 (p. Phe616Leu) and TLR9 rs5743836 promoter area polymorphism were associated with earlier spontaneous HBeAg seroconversion. Toll-like receptor 4 rs4986790 (p. Asp299Gly) was associated with HBsAg serodearance/seroconversion in chronic HBV patients. Toll-like receptor 5 rs5744174 (p. Phe616Leu) was associated with higher IFN-γ production in chronic HBV-infected patients.